The effect of using Ground Granulated Blast Furnace Slag (GGBFS) in mortar mixes on setting time - Irawan, Dafid; Priyandoko, Gigih; Moreira Loe, Febriana Dominggas; Ayuningtyas, Firda Hani (SINERGI, 2025)
This study highlights the potential of GGBFS as an additive to speed up cement hydration, improve cement durability, and lessen the environmental impact of more widely used cement. This study aims to analyze the effect of varying percentages of GGBFS on the setting time of mortar. We chose GGBFS as an additive because of its environmentally friendly properties and its efficiency in enhancing the mechanical characteristics of mortar. This study uses an experimental method with variations in the GGBFS composition of 0%, 10%, 20%, and 30%. We conducted laboratory tests using a Vicat apparatus on 12 samples to measure the initial and final setting times and analyze the slump value. The research results show that the addition of GGBFS significantly affects the setting time of the mortar. A GGBFS composition of 10% resulted in the fastest initial setting time (145 minutes) and the fastest final setting time (245 minutes), compared to the control without GGBFS. (215 menit dan 315 menit). Slump testing indicates that GGBFS reduces the slump value by up to 20% (8.7 cm) but increases at a 30% composition. (11.3 cm). ANOVA analysis shows a significant effect with a calculated F-value (12.14) greater than the F-table (4.07).